2020
DOI: 10.1038/s41598-020-68838-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–nitrogen plasma assisted synthesis of titanium dioxide with enhanced performance as anode for sodium ion batteries

Abstract: Sodium ion batteries are considered as one of the most promising energy storage devices as lithium ion batteries due to the natural abundance of sodium. tio 2 is very popular as anode materials for both lithium and sodium ion batteries because of the nontoxicity, safety and great stabilities. However, the low electronic conductivities and inferior sodium ion diffusion make it becoming a great challenge to develop advanced tio 2 anodes. Doping heteroatoms and incorporation of defects are believed to be great wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Furthermore, as shown at Figure 3d, the C-TiO2 nanoparticles were terminated by highly crystalline sharp facets, while arrows at Figure 3 e and f indicate the formation of a distorted surface layer of ~1 nm thickness in the case of H-TiO2 and N-TiO2. This phenomenon is well known and discussed for black TiO2 and was also reported by Wang et al, where surface distortion in TiO2 nanoparticles was also observed after hydrogen and nitrogen plasma treatments [17,33]. The absorption properties of the TiO2 powders derived from the diffuse reflectance measurements at room temperature are summarized in Figure 4.…”
Section: Characterizationssupporting
confidence: 74%
“…Furthermore, as shown at Figure 3d, the C-TiO2 nanoparticles were terminated by highly crystalline sharp facets, while arrows at Figure 3 e and f indicate the formation of a distorted surface layer of ~1 nm thickness in the case of H-TiO2 and N-TiO2. This phenomenon is well known and discussed for black TiO2 and was also reported by Wang et al, where surface distortion in TiO2 nanoparticles was also observed after hydrogen and nitrogen plasma treatments [17,33]. The absorption properties of the TiO2 powders derived from the diffuse reflectance measurements at room temperature are summarized in Figure 4.…”
Section: Characterizationssupporting
confidence: 74%
“…As shown in Figure b, the b-Si peak located at 69.3° is the (400) facet of crystalline Si . The peaks at 2θ = 25 and 37.5° are (101) and (004) planes of the anatase phase TiO 2 . It means that the ALD-deposited TiO 2 was transferred from the amorphous phase (see Figure S5) to the anatase phase during further fabrication procedure.…”
Section: Resultsmentioning
confidence: 95%
“…40 The peaks at 2θ = 25 and 37.5°are (101) and (004) planes of the anatase phase TiO 2 . 42 It means that the ALDdeposited TiO 2 was transferred from the amorphous phase (see Figure S5) to the anatase phase during further fabrication procedure. The remaining peaks in the diffractograms belong to the ReS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, anatase has a higher theoretical storage capacity of 335 mAh g −1 and a lower energy barrier for the insertion of Na + than rutile and amorphous TiO 2 [22]. Nano-sized particles offer a high surface-to-volume ratio to facilitate ion transport, overcoming the long diffusion time of large Na + ions into the TiO 2 crystal structure [24,25]. In addition, small particle sizes reduce the effect of mechanical strain during the intercalation/deintercalation of Na + because they enable the dissipation of mechanical stress via the surface.…”
Section: Introductionmentioning
confidence: 99%